Frequency of abnormal branching pattern of axillary artery: a cadaveric study - Rani, Pooja; Dhurandhar, Diwakar; Chauhan, Renu (International Journal of Research in Medical Sciences, 2017)
Many authors suggest that abnormal branching pattern of axillary artery is very common. This compelled us to explore the axillary region of 20 formalin fixed cadavers of either sex to note the frequency of unusual branching of axillary artery over a period of five years. Axillary artery branched normally as described in various textbooks of Anatomy in thirty nine (97.5%) out of forty axillae examined. Only in one axilla (2.5%), it was observed that the second part of axillary artery branched unusually whereas on the other side it branched normally. Knowledge of such abnormal presentation of the axillary artery in the era of reconstructive surgeries is of great help to the interventionist so as to avoid any vascular catastrophe resulting in some kind of mishap. Awareness of such unusual branching pattern of axillary artery is also of great importance to vascular surgeons and radiologists dealing with this region. Embryological origin and the clinical relevance of the abnormality encountered in the branching pattern of the axillary artery in the present study have been discussed in the paper.